PENDAMPINGAN DALAM MEMBUAT DAN MENGGUNAKAN MEDIA PEMBELAJARAN BAHASA INGGRIS BAGI GURU TK DAN SD DI WILAYAH CIHAMPELAS KABUPATEN BANDUNG BARAT - Sri Supiah Cahyati; Aseptiana Parmawati; Nai Supartini Atmawidjaja (IKIP SILIWANGI, 2020)
English learning is a local content at the elementary level. Our interest in the PKM program is due to the initial findings that most of teachers who teach English at kindergarten or elementary levels only rely on the existing worksheet. In addition, teachers still find it difficult to find or use learning media that is in line with the learning theme. The main objective in this activity is to provide assistance in making and using English learning media. The method of implementing this activity is in the form of in-service training programs, namely training for kindergarten and elementary school teachers in Cihampelas sub-district. Based on the results of the questionnaire, it can be concluded that the training material is very useful for participants in enhancing creativity, besides that the participants also think that the teaching media used are easy to make.